Principles and Practice of Community Medicine - Rahim Asma; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2008)
This concise textbook presented in a lucid style in Community Medicine. Important topics like General Epidemiology, Environment, Hospital Hygiene, Immunisation etc. which are often poorly dealt with in most of the currently available books. All topics have been treated with equal importance. The reader may find the presentation a little different as the key points are highlighted for holding readers immediate attention. This book is sure to serve as a quick reference during exams for the Medical students. It is my strong intuition that this book will be handy for allied medical disciplines like Dentistry, Nursing, Pharmacy and even Medical Officers from the Health services.
Keywords: Community Medicine; Electronic books